Implementation Of Inclusive Education Policy (Case Study At Sdn Sukabumi Selatan 07 West Jakarta) - Nurinna Azizi; Neneng Sri Rahayu; Ratri Istania (Eduvest - Journal of Universal Studies, 2025)
This study investigates the implementation of inclusive education at SDN Sukabumi Selatan 07 in West Jakarta, where participation of students with special needs continues to increase. Despite this positive development, the school’s education report, particularly in terms of inclusivity climate has not shown corresponding improvement. Using a qualitative approach, the research draws on interviews, observations, and supporting secondary data, guided by Van Meter and Van Horn’s policy implementation theory. The findings reveal that the implementation of inclusive education remains suboptimal, largely due to limitations in resources and the technical capacity of implementers, both in terms of the characteristics of implementing agents and their tendencies or dispositions. Key resource challenges include the unavailability of Special Education Support Teachers, lack of targeted budget allocations, and insufficient accessible infrastructure. In addition, gaps in teacher’s understanding and technical ability to apply differentiated and adaptive teaching methods hinder effective inclusion. These issues hinder the development of a supportive school environment for maximizing the potential, interests, and talents of these students with special needs. To address these issues, the study recommends a series of strategic actions: optimizing the allocation and use of BOP and BOSP funding to support inclusive services, expand collaboration networks with higher education institutions through internship programs for pre-service teachers, and enhance the utilization of the resource room to function as a Learning and Intervention Center for students with special needs.